2016
DOI: 10.1161/circresaha.115.305206
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of DNA Methylation in Cardiovascular Risk and Disease

Abstract: Epidemiological studies have demonstrated that genetic, environmental, behavioral, and clinical factors contribute to cardiovascular disease (CVD) development. How these risk factors interact at the cellular level to cause CVD is not well known. Epigenetic epidemiology enables researchers to explore critical links between genomic coding, modifiable exposures, and manifestation of disease phenotype. One epigenetic link, DNA methylation, is potentially an important mechanism underlying these associations. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(78 citation statements)
references
References 152 publications
(211 reference statements)
0
77
0
1
Order By: Relevance
“…2732 Higher exposure to air pollution has consistently been shown to be associated with DNA methylation changes. 24,30,33,34 For example, Wang et al reported that per interquartile range increase (26.78µg/m 3 ) in 24-hour exposure to fine particulate matter (PM 2.5 ), angiotensin-converting enzyme DNA methylation (%5mC) was 1.12% lower. 24 Breton et al recently found that first trimester prenatal exposure to multiple pollutants was associated with lower DNA methylation of a retrotransposon repetitive element found throughout the genome (long-interspersed nuclear element 1 [LINE1]) and that O 3 exposure later on in pregnancy was associated with higher LINE1 methylation levels.…”
Section: Differential Exposures and Dna Methylationmentioning
confidence: 99%
“…2732 Higher exposure to air pollution has consistently been shown to be associated with DNA methylation changes. 24,30,33,34 For example, Wang et al reported that per interquartile range increase (26.78µg/m 3 ) in 24-hour exposure to fine particulate matter (PM 2.5 ), angiotensin-converting enzyme DNA methylation (%5mC) was 1.12% lower. 24 Breton et al recently found that first trimester prenatal exposure to multiple pollutants was associated with lower DNA methylation of a retrotransposon repetitive element found throughout the genome (long-interspersed nuclear element 1 [LINE1]) and that O 3 exposure later on in pregnancy was associated with higher LINE1 methylation levels.…”
Section: Differential Exposures and Dna Methylationmentioning
confidence: 99%
“…Epigenomic research is now rapidly progressing from candidates epigenetic studies in a few individual cells towards the investigation of epigenomic variation in the population (93). Epigenome-wide association studies (EWAS) provide a systematic approach, comparable to GWAS, focused on uncovering epigenetic variants associated with diseases or phenotypes of interest by taking advantage of microarrays capable of measuring DNA methylation at up to 850,000 sites (93).…”
Section: Epidemiological Perspectivementioning
confidence: 99%
“…Epigenome-wide association studies (EWAS) provide a systematic approach, comparable to GWAS, focused on uncovering epigenetic variants associated with diseases or phenotypes of interest by taking advantage of microarrays capable of measuring DNA methylation at up to 850,000 sites (93). These EWAS have identified hundreds of CpGs, including HIF3A (hypoxia-inducible factor 3A), associated with body mass index (9496), ABCG1 (ATP-binding cassette subfamily G member 1 , PHOSPHO1 (phosphoethanolamine/phosphocholine phosphatase), SOCS3 (suppressor of cytokine signaling-3) , SREBF1 (sterol regulatory element-binding protein 1), and TXNIP (thioredoxin-intereacting protein) with risk of future type 2 diabetes (97).…”
Section: Epidemiological Perspectivementioning
confidence: 99%
See 2 more Smart Citations